A Conjugated Figure‐of‐Eight Oligoparaphenylene Nanohoop with Adaptive Cavities Derived from Cyclooctatetrathiophene Core. (20th December 2021) - Zhan, Lijie; Dai, Chenshu; Zhang, Guohui; Zhu, Jun; Zhang, Shaoguang; Wang, Hua; Zeng, Yi; Tung, Chen‐Ho; Wu, Li‐Zhu; Cong, Huan
Abstract: A fully conjugated figure‐of‐eight nanohoop is presented with facile synthesis. The molecule's lemniscular skeleton features the combination of two strained oligoparaphenylene loops and a flexible cyclooctatetrathiophene core. Its rigid yet guest‐adaptive cavities enable the formation of the peanut‐like 1:2 host–guest complexes with C60 or C70, which have been confirmed by X‐ray crystallography and characterized in solution. Further computational studies suggest notable geometric variations and non‐covalent interactions of the cavities upon binding with different fullerenes, as well as overall conjugation comparable to cycloparaphenylenes. Abstract : Based on strained oligoparaphenylene loops and a flexible cyclooctatetrathiophene moiety, a fully conjugated bis‐macrocycle is efficiently constructed, and possesses rigid and guest‐adaptive cavities. Its peanut‐like 1:2 host–guest complexes with C60 or C70 have been isolated and characterized, respectively.